Change in body image flexibility and correspondence with outcomes in a digital early intervention for eating disorders based on acceptance and commitment therapy. (March 2023) - Merwin, Rhonda M.; Nikolaou, Patrisia; Moskovich, Ashley A.; Babyak, Michael; Smith, Patrick J.; Karekla, Maria
Abstract: Body image flexibility (BIF) has been suggested as a transdiagnostic process of change in eating disorder (ED) interventions, but data remain sparse. The current study examined the relationship between BIF and treatment effects in a randomized controlled trial comparing a digital ACT-based intervention to a waitlist control for early ED intervention. Women and girls with elevated Weight Concern Scale (WCS) scores were randomized to either the ACT intervention or a waitlist control. Linear regression models were used to examine the impact of treatment on WCS scores controlling for age and body-mass index and BIF was examined as a mediator of change. Change in BIF was also examined as a predictor of Eating Disorder Examination-Questionnaire (EDE-Q) global scores at 1-month in the ACT condition. ACT participants had greater reductions in WCS scores, an effect partially mediated by BIF and concentrated almost entirely in the ACT condition. Increased BIF from baseline to end-of-treatment also predicted lower EDE-Q scores at 1-month post-intervention. The current study suggests additional research exploring BIF as a process of change in EDs is warranted and could expand understanding of how treatment works or treatment options. Additional studies with more frequent, complete and concordant assessments between groups are needed. Highlights: Body image flexibility increased in an early intervention for eating disorders. Body image flexibility partially mediated the effects of intervention on weight concerns. Increased body image flexibility predicted lower eating disorder symptoms at 1-month.